Role of Adiponectin in the Treatment of Age-Related Macular Degeneration and Other Metabolic Disorders - Singh, Anusha; Bora, Nalini S; Bora, Puran S (Disease and Health Research: New Insights Vol. 10, 2024)
Adiponectin (APN) has been thoroughly investigated for its role in various human disorders. It is fascinating to note that this peptide plays an essential role as a therapeutic agent to cure a plethora of disorders. The aim of the study is to elucidate this peptide's applications and therapeutic potential of this peptide, demonstrating its involvement in age-related macular degeneration (AMD) and other metabolic disorders. APN has been correlated with many ocular disorders and metabolic disorders. The localization and expression of APN in various tissues were the first markers of its local actions. Screening this peptide on a wider platform helps to confirm its application as a novel peptide in various diseases. Altered levels of APN have been well elucidated in the progression of metabolic disorders, and its targeted administration has resulted in combating dysregulation of biochemical and molecular pathways involved in disease pathology. A close association of oxidative stress is also known to contribute to the onset of retinal disorders. Among various treatments, APN has demonstrated a promising response in the context of wet AMD; however, further studies are required to fully elucidate its potential in humans.